2022
DOI: 10.1186/s13054-022-04154-2
|View full text |Cite
|
Sign up to set email alerts
|

The glycocalyx as a permeability barrier: basic science and clinical evidence

Abstract: Preclinical studies in animals and human clinical trials question whether the endothelial glycocalyx layer is a clinically important permeability barrier. Glycocalyx breakdown products in plasma mostly originate from 99.6–99.8% of the endothelial surface not involved in transendothelial passage of water and proteins. Fragment concentrations correlate poorly with in vivo imaging of glycocalyx thickness, and calculations of expected glycocalyx resistance are incompatible with measured hydraulic conductivity valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 76 publications
0
26
0
Order By: Relevance
“…17,23 While the precise ultrastructural contribution of the pulmonary EGCX (and concurrently, HS) to endothelial permeability is debated, it serves a major role in regulating mechanosignaling pathways that impact endothelial barrier function. 14,37 There are few clinical studies that have specifically and simultaneously measured PGs (syndecan-1) and the ultrastructural characteristics of GAGs (HS, HA, and CS) in adult or pediatric ARDS. In a small cohort of adults intubated for respiratory failure, plasma HS concentrations (particularly highly sulfated HS disaccharides) were higher among patients with nonpulmonary sepsis (compared to healthy controls).…”
Section: Discussionmentioning
confidence: 99%
“…17,23 While the precise ultrastructural contribution of the pulmonary EGCX (and concurrently, HS) to endothelial permeability is debated, it serves a major role in regulating mechanosignaling pathways that impact endothelial barrier function. 14,37 There are few clinical studies that have specifically and simultaneously measured PGs (syndecan-1) and the ultrastructural characteristics of GAGs (HS, HA, and CS) in adult or pediatric ARDS. In a small cohort of adults intubated for respiratory failure, plasma HS concentrations (particularly highly sulfated HS disaccharides) were higher among patients with nonpulmonary sepsis (compared to healthy controls).…”
Section: Discussionmentioning
confidence: 99%
“…This results, in part, owing to loss of albumin-mediated control of intracellular calcium. 24 In addition, loss of syndecan expression hinders mechanotransduction signaling that is crucial to maintenance of cytoskeletal structure and junctional protein expression. Activated leukocytes secrete soluble factors that can directly disrupt paracellular vascular endothelial cadherin linkages.…”
Section: Glycocalyx Damage In the Development Of Eotmentioning
confidence: 99%
“…Third, glycocalyx shedding results in loss of vascular barrier integrity and hyperpermeability. This results, in part, owing to loss of albumin-mediated control of intracellular calcium 24 . In addition, loss of syndecan expression hinders mechanotransduction signaling that is crucial to maintenance of cytoskeletal structure and junctional protein expression.…”
Section: The Endotheliopathy Of Traumamentioning
confidence: 99%
“…It is a multi-component layer composed of proteoglycans (including syndecan-1) and glycoproteins, anchored to the endothelium by glycosaminoglycans. Although its role in vascular permeability has recently been debated [ 41 ], the glycocalyx mediates several key physiological processes, such as vascular barrier function, hemostasis, autoregulation, leukocyte, and platelet adhesion, and also transmission of shear stress to the underlying endothelium [ 42 ]. Jung et al showed that high syndecan-1 levels, reflecting glycocalyx shedding, were predictive of short-term mortality in early AMICS [ 43 ].…”
Section: Introductionmentioning
confidence: 99%